Cardiovascular disease in human immunodeficiency virus-infection as a cause of hospitalization: a case-series in a General Hospital in Peru. - Valenzuela-Rodríguez, Germán (2015)
Background: Cardiovascular disease in the context of human immunodeﬁciency virus infection has become a major clinical concern in recent years. In the current report we assess hospitalizations due to cardiovascular disease in human immunodeﬁciency virus patients in a Social Security reference hospital in Peru. Methods: A retrospective study was carried out between January 1996 and December 2012 in a General Hospital in Lima, Peru. Results: We included 26 patients hospitalized due to cardiovascular disease. Mean age was 46.3 years (SD 12.5), predominantly male (57.7%). Ten patients (38.4%) were in Acquired Immunodeﬁciency Syndrome stages. Seventeen (65.4%) received high-active-antiretroviral therapy. Eleven (42.3%) had cardiac involvement and 15 (57.7%) had non-cardiac vascular involvement. The most frequent causes of cardiac involvement were pericardial effusion and myocardial infarction. On the other hand, deep vein thrombosis and stroke were the most frequent for non-cardiac vascular involvement. Conclusions: Cardiovascular disease is an important cause of hospitalization in Peruvian human immunodeﬁciency virus patients, with differences between immunosuppression stages. Further studies analyzing associated factors are warranted.